Gastroprotective activity of Polygonum chinense aqueous leaf extract on ethanol-induced hemorrhagic mucosal lesions in rats - Abdulla, Mahmood Ameen; Ismail, I.F.; Golbabapour, S.; Hassandarvish, P.; Hajrezaie, M.; Majid, Nazia Abdul; Kadir, F.A.; Al-Bayaty, F.; Awang, K.; Hazni, H. (Hindawi, 2012)
Polygonum chinense is aMalaysian ethnic plant with various healing effects. This study was to determine preventive effect of aqueous leaf extract of P. chinense against ethanol-induced gastric mucosal injury in rats. Sprague Dawley rats were divided into seven groups. The normal and ulcer control groups were orally administered with distilled water. The reference group was orally administered with 20mg/kg omeprazole. The experimental groups received the extracts 62.5, 125, 250, and 500 mg/kg, accordingly. After sixty minutes, distilled water and absolute ethanol were given (5 mL/kg) to the normal control and the others,respectively. In addition to histology, immunohistochemical and periodic acid schiff (PAS) stains, levels of lipid peroxidation,malondialdehyde (MDA), antioxidant enzymes, and superoxide dismutase (SOD) were measured. The ulcer group exhibited severe mucosal damages. The experimental groups significantly reduced gastric lesions and MDA levels and increased SOD level. Immunohistochemistry of the experimental groups showed upregulation and downregulation of Hsp70 and Bax proteins, respectively. PAS staining in these groups exhibited intense staining as compared to the ulcer group. Acute toxicity study revealed the nontoxic nature of the extract. Our data provide first evidence that P. chinense extract could significantly prevent gastric ulcer.